Geographical genetic variability in vervet monkey (Cercopithecus aethiops) populations - Matlala, Moloko Jacob (University of Limpopo, 2001)
A South African rehabilitation centre for illegally kept vervet monkeys required an evaluation of the genetic status of vervet monkeys , to determine whether animals from different geographical areas may be kept in the same enclosures and mixed during release back into the wild. Animals originating from three geographical regions (the former Transvaal, KwaZulu-Natal and the Eastern Cape) were studied using biochemical genetic and morphological approaches to address this question. The most prominent trend from allozyme data was derived from the locus PRT-2 (an unspecified serum protein), where each of the three populations could be characterized by the absence or presence of unique alleles. A significant deviation of genotypes from Hardy Weinberg equilibrium was found at the PGD-1 locus in all the populations studied. Nevertheless, statistical coefficients indicated little genetic divergence, with genetic distance values of 0.001-0.003, gene flow values of 4.300 - 16.310 and an overall fixation index value of 0.046. Average heterozygosity did not differ appreciably among populations (2.5-3.3%). The morphological study identified suitable traits, free from the influence of growth allometry, which can be used for inter-population comparisons. No significant morphological differences between conspecific populations were however found. It is concluded that vervet monkeys from the species' wider distribution range is relatively monotypic, but that monkeys from different geographical areas should not be unduly mixed, pending the results of finer grained molecular studies.
Thesis (M.Sc. (Zoology)) --University of Limpopo, 2001.
Keywords: Geographical genetic variability; Vervet monkey (Cercopithecus aethiops); Vervet monkey -- South Africa; Vervet monkey -- Nature conservation